Physical activity as a basis for the health of students of a pedagogical university - Koshkina N.A.; Popova G.A.; Shushkanova E.G. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to еvaluation of students’ physical activity and its correlation with various aspects of a healthy lifestyle. Methods and structure of the study. One hundred and fifty students in their first year of study in the pedagogical program at Vyatka State University in Kirov participated in the experiment. To evaluate the elements of a healthy lifestyle, we employed the questionnaire «Prozozh». The level of activity of the participants was assessed using the questions from the SAN methodology. The vitality and strength indices were calculated using standard methods. The statistical analysis was conducted using the Jamovi software (version 1.6). The correlation between the components of a healthy lifestyle and the activity scale was determined using the Spearman’s rank correlation coefficient. Results and conclusions. The findings demonstrate the average level of healthy lifestyle components among first-year students. A responsible approach to health was observed in 50% of the participants. The majority of respondents (66%) do not engage in regular physical activity or exercise. Insufficient sleep was reported by 59% of the participants, which may have a negative impact on their performance and overall well-being. A positive correlation has been established between the indicators of physical activity and the SAN activity scale: the higher the physical activity score, the higher the overall activity score, and vice versa (r=0,161; p=0,049). Therefore, increasing physical activity and implementing educational initiatives to promote healthy lifestyle habits are crucial for maintaining the health of students.